Clinical study of lipid abnormalities in anti-retroviral treatment-naive HIV patients - Gowdaiah, Prakash Kikkeri; Reddy, Sandeep Sreerama; Joseph, Jacob (International Journal of Advances in Medicine, 2017)
Background: HIV infection has reached pandemic proportions ever since the first case was reported in 1981. Now, it continues to be the most important communicable disease in India with its associated high morbidity, mortality and treatment costs. With the introduction of highly active antiretroviral therapy, people with HIV infection now live longer. And the major contributors to morbidity and mortality are drug toxicities and metabolic derangements due to HAART, not the opportunistic infections. Dyslipidemia is one such metabolic derangement which occurs either as an adverse effect of ART drugs or due to HIV infection per se. This study was undertaken to address the second issue, as the data from India is limited. Methods: 80 newly detected HIV patients who were naïve to antiretroviral drugs and who did not have exclusion criteria like prior diabetes mellitus, thyroid disease, hepatitis, pregnancy etc. were selected randomly and enrolled into the study over a year. A baseline complete hemogram with CD4 cell count and all necessary biochemical tests were done. The patients were grouped according to WHO staging. 80 age and sex matched healthy controls were also enrolled during the same period and they were also subjected to similar investigations. The various lipid parameters were analysed and compared between two groups as well as among patients with different WHO stages and CD4 lymphocyte counts. Results: 80 cases and 80 controls who were age and sex matched were enrolled. Mean BMI was significantly less in cases. Among cases, 72 patients (90%) had CD4 count <200 cells/mm3 and 59 of them had an opportunistic infection. The mean triglyceride (TG) was significantly higher in the HIV-infected patients than in the controls, 176.125 mg/dL vs. 119.225 mg/dL with a P value = 0.02. The HIV-infected patients also had significantly lower mean HDL-C 33.58 mg/dL vs. 48.38 mg/dL with a P value = 0.04. On subgroup analysis in the HIV-infected patients, the mean serum triglyceride and VLDL levels were significantly higher in those with CD4+ cell count <200 cells/mm3 compared to those with CD4+ cell count of 200 to ≥500 cells/mm3, with a P value of 0.04 & 0.003 respectively. Similarly, the same lipid parameters showed a rising trend in serum values as the stage of HIV infection advanced. Conclusions: It can be concluded from the study that dyslipidemia manifesting as significant hypertriglyceridemia and low HDL cholesterol is common among treatment naïve HIV infected patients and it worsens with advanced stages of illness with decreasing CD4 cell count. Hence, a baseline lipid profile should be obtained in all HIV infected patients before initiating HAART.